Kendala Dalam Pembelajaran Jarak Jauh Pada Masa Pandemi Covid-19 (Studi Kasus di SDN Wanatirta 04 Kecamatan Paguyangan Kabupaten Brebes) - Azqia, Maulia Azqia (Universitas Sebelas Maret, 2020)
The Covid-19 pandemic that has hit the world, including Indonesia, requires taking a stand in preventing wider transmission, including the education sector. In this regard, the Ministry of Education and Culture has taken a firm stance through several circular letters relating to education policies in the emergency period of the spread of Covid-19. The distance learning process is a solution that is not yet optimal in its implementation. There are things that must be considered in this distance learning, among others, the quality of teacher resources must be improved, both in terms of content and methodology as well as in terms of the use of information technology. In addition, students are also less active in participating in this distance learning, both due to an unstable internet network and in terms of providing a limited internet quota. The purpose of writing this article is to study and understand the problems in learning activities during a pandemic, namely distance learning so that students can participate actively and interestingly. This study used a qualitative and observative approach. The results of this study prove that distance learning (PJJ) during the Covid-19 pandemic caused various responses and changes to the learning system that could affect the learning process and the level of development of students in responding to the material presented.